(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Background: Sepsis is a major cause of morbidity and mortality worldwide, with ICU patients at particularly high risk. Nurses are pivotal to early detection and prevention, yet their knowledge, practices, and barriers in Saudi hospitals remain underexplored. Objective: To evaluate ICU nurses’ knowledge, practices, and barriers in sepsis detection and prevention across tertiary hospitals in Saudi Arabia. Methods: A cross-sectional, multi-center study was conducted among 461 ICU nurses in three Riyadh hospitals (March–June 2025). Data were collected via structured questionnaires assessing demographics, sepsis knowledge, practice adherence, and perceived barriers. Facility surveys and focus group discussions supplemented quantitative findings. Data were analyzed using descriptive statistics, chi-square, and ANOVA. Results: Of the 461 nurses surveyed, 62.7% were female, 58.8% expatriates, and 71.2% held a bachelor’s degree. Mean sepsis knowledge score was 63.5% (SD=12.4), with significant variation by education level (p<0.01). Only 54.1% consistently applied standardized screening tools, and 48.3% adhered fully to sepsis bundle protocols. Barriers included heavy workload (72.6%), inadequate training (59.8%), and resource limitations (41.5%). Nurses with specialized critical care training scored significantly higher in both knowledge (72.1% vs. 59.4%, p<0.001) and practice adherence (65.2% vs. 46.8%, p<0.001). Conclusion: Saudi ICU nurses demonstrate moderate knowledge and practice levels in sepsis care, with gaps influenced by education, training, and institutional support. Strengthening structured sepsis education, ensuring bundle compliance, and integrating digital early-warning systems could significantly improve patient outcomes.